2020
DOI: 10.3390/ani10111995
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Genotype at CSN3 Gene, Milk Composition, Coagulation and Cheese-Yield Traits of the Sardo-Modicana, an Autochthonous Cattle Breed from the Sardinia Region, Italy

Abstract: The Sardo-Modicana is a local cattle breed from Sardinia, Italy. No information about its dairy potential is available in the literature. This study investigated the genotype at the CSN3 gene and milk traits of the Sardo-Modicana cattle breed. Fifty-four cows were sampled for DNA extraction and genotyping at the κ-casein gene locus, CSN3. Forty individual milk samples were analyzed for milk composition, milk coagulation properties and cheese yield (CY%). All the Sardo-Modicana cows were BB homozygotes at CSN3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In each farm, one to thirty-one female cattle were randomly chosen. Cows were managed under extensive farming systems based on mountainous territories with low agricultural productivity and typically associated with goat farming 9 . DNA was extracted from leukocytes using the Puregene DNA isolation kit (Gentra, Qiagen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In each farm, one to thirty-one female cattle were randomly chosen. Cows were managed under extensive farming systems based on mountainous territories with low agricultural productivity and typically associated with goat farming 9 . DNA was extracted from leukocytes using the Puregene DNA isolation kit (Gentra, Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…Traditionally, sheep and goat farming have had an important impact in the rural economy of Sardinia 7 , 8 . In addition, three local cattle breeds are currently reared in Sardinia: the Sarda, the Sardo Bruna and the Sardo Modicana 9 . Sarda cattle are small sized, with high hardiness and resistance.…”
Section: Introductionmentioning
confidence: 99%
“…A high degree of polymorphism in each of the four genes has a different effect on cow productivity and milk quality. At present, the polymorphism of the CSN3 gene has been intensively studied, due to its responsibility for the k-casein expression, with a special location in the structure of casein micelles and its technological functionality [11][12][13]. Casein micelles are colloidal particles of 50 to 500 nm in diameter with an average mass of 10 6 to 10 9 Da [14].…”
Section: Introductionmentioning
confidence: 99%
“…This results in the formation of a paracasein matrix, which includes fat globules and part of the soluble phase of milk [17]. Thus, k-casein plays a key role in cheese production, influencing the yield and characteristics of the clot, while its genetic polymorphism may have a significant impact on the technological process [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that allele A of the kappa-casein gene is associated with increased milk yield in cows, and allele B is associated with a high fat and protein content in milk and better technological performance for the production of hard cheeses (Kopylov, 2010;Huiam et al, 2018). Therefore, the milk of cows with the genotype BB and AB capa-casein is characterized by a higher protein content and under the influence of enzyme rennet coagulates faster than the milk of cows with AA genotype (Pazzola et al, 2020;Doosti et al, 2011). Thus, to date, according to the literature, it is known that in Ukraine genetic study of cows was carried out by Suprovych & Mokhnachova (2017), who studied the polymorphism of kappa-casein (CSN3) genes in cows of the grey Ukrainian breed The researchers found that in cows of the grey Ukrainian breed the incidence of A allele of the kappa-casein CSN3 gene associated with increased milk yield was 60.7% and was significantly higher than the incidence of B allele associated with high protein content in milk and the best technological indicators for the production of hard cheeses were found in 39.3% of the population of this cow.…”
Section: Introductionmentioning
confidence: 99%